A fluorescence-based assay to monitor transcriptional activity of NFAT in living cells - Rinne, Andreas (Blackwell Science Inc, 2010)
Ca(2+)-sensitive NFAT (nuclear factor of activated T-cells) transcription factors are implicated in many pathophysiological processes in different cell types. The precise control of activation varies with NFAT isoform and cell type. Here we present feasibility of an in vivo assay (NFAT-RFP) that reports transcriptional activity of NFAT via expression of red fluorescent protein (RFP) in individual cells. This new tool allows continuous monitoring of transcriptional activity of NFAT in a physiological context in living cells. Furthermore, NFAT-RFP can be used simultaneously with NFAT-GFP fusion proteins to monitor transcriptional activity and subcellular localization of NFAT in the same cell.